COMPARISON STUDY OF THE SHEAR BOND STRENGTH BETWEENPOLYETHER AND ADDITION SILICONE IMPRESSIONMATERIALS - Oboudi, Saad F (Al-Nahrain Journal of Science, 2018)
The impression material is used mainly in the area of removable partial and complete denture and in the construction of inlays, crowns and bridges. They are used also in dental laboratories for duplicating master casts. Recent studies have evaluated the bond strength of selected impression materials. This research was performed to study the shear bond strength of impression materials to tray by testing forty samples, each of which consisted of two blocks of acrylic with the impression material sandwiched between them. Tray adhesive was used to increase adhesion between impression material and custom tray. Also this research showed that by the use of perforation impression materials adhere firmly to the impression trays. Therefore perforation - adhesive combination gave acceptable results. Experimental results indicated that polyether impression material showed higher shear bond strength values to cold-cure acrylic than addition silicone impression material for both control and perforated samples without adhesive application. The shear mean bond strength values of polyether to the tray material after adhesive application were decreased. While, the shear mean bond strength increased significantly when addition silicone was used with the adhesive and with the combination samples.